The compressibility behavior of natural clay soil with sodium chloride & distilled water - Nur Nadiah, Mohd Nazim (2012)
Nowadays waste is increasing day by day as a result of human activity and its disposal becomes a major problem. Waste disposal by landfill is the most popular method, which is currently in practice. Landfills are often lined with clayey liner material to prevent migration of contaminants into the environment. For cheaper alternatives, natural soils are used as liner materials. In the case of landfills constructed near coastal areas, intrusion of seawater might affect the stability of the liner system. This study presents the effect of sodium chloride (NaCl) solution and distilled water towards the compressibility behavior of natural soil (KB soil) from saturated slurried condition. The pressure-void ratio and pressure-water content relationships were then established using double-oedometer tests. Furthermore, the effect of NaCl and distilled water on the physical properties of KB soil was also determined. The liquid limit and plastic limit were slightly higher than the values obtained using distilled water. On the other hand, the double-oedometer test results showed that the pressure-void ratio relationship for distilled water was higher than that of NaCl. Similar trend was also observed in the pressure-water content relationship. Test results indicated that cation concentration contained within the seawater affects the plasticity and compressibility characteristics of KB soil.